Indira Awaas Yojna in Uttar Pradesh and Bihar. - Sikligar, P.C (2009)
Housing is one of the basic needs for human survival. Indira Awaas Yojana (IAY) is one of the centrally sponsored housing schemes in India for the marginal income groups who are unable to construct a decent habitat due to economic constraints and poverty. This paper concentrates on various issues like selection process of the beneficiaries, role of elected representatives especially in the Gram Sabha and at the Gram Panchayat level in case of choosing the beneficiaries, area covered by the beneficiaries under house construction, gender issue in case of allotment of the house, beneficiaries’ contribution in planning and construction of the house, utilization of assistance, sources of additional amount borrowed by the beneficiaries, status of construction, possession of the house, monitoring, etc along with perception of the beneficiaries and non- beneficiaries about the scheme in Bihar and Uttar Pradesh, which are ahead in the demand for housing due to high populations. The study1 examines sufficiency of the allocation fixed by the government for construction of new house and up-gradation of old house. The manipulation in selection process delineates deserving families from the grave of the scheme and finds that benefit has been given to those who further bifurcated into the nuclear families. The cost of materials, transportation and wages of labourers becomes challenging for the beneficiaries to complete the house with in the allocation fixed by the government.